Effect of Acupuncture and Foot Massage for Treatment of Diabetic Peripheral Neuropathy - Bunrin, Siwapol; Sakunasing, Jittsakul (Journal of Health Science of Thailand, 2017)
The objective of this experimental study was to evaluate the therapeutic effect of acupuncture and foot massage for insensate foot in diabetic peripheral neuropathy (DPN) in 60 diabetes mellitus (DM) type II patients attending Diabetes Clinic of Roi-et Hospital. In the first group, 30 patients received acupuncture once a week for five weeks. In the second group, 30 patients received foot massage once a week for five weeks. Both groups also received the same conventional treatment. Evaluation of insensate feet with Semmes -Weinstein monofilament was carried out one week before and after treatment. Repeated Measure Analysis of Variance was employed in statistical analysis. The results showed statistically significant improvements of the insensate feet in both groups. The difference of the two group was statistically significant whearas more effectiveness was shown in the acupuncture group. In all, acupuncture and foot massage may show good effects for insensate foot in diabetic peripheral neuropathy.